2019
DOI: 10.1007/s10344-019-1271-9
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned food aversion mediated by odour cue and microencapsulated levamisole to avoid predation by canids

Abstract: Worldwide, predators and humans are in conflict for resources such as game species or livestock, especially in the case of medium-large wild canids. One non-lethal method to reduce predation is conditioned food aversion (CFA), in which animals learn to avoid a food due to the illness after its ingestion, caused by the addition of an undetected chemical compound. Food aversion can be enhanced by adding an artificial odour cue, in a process known as taste-potentiated odour aversion (TPOA). We carried out an expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 44 publications
(70 reference statements)
0
13
1
1
Order By: Relevance
“…Contrary to studies with other aversive substances reporting that an odor cue can enhance the food rejection, here with thiram the TH group showed stronger aversion than the THO group. Recently, we showed an enhanced aversion in penned dogs using levamisole plus an odor cue, increasing the strength and time to extinction in a taste‐potentiated odor aversion procedure. It has been suggested that the strong flavor of levamisole acted as a strong cue enhancing the aversion to the weaker cue, the vanilla odor .…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Contrary to studies with other aversive substances reporting that an odor cue can enhance the food rejection, here with thiram the TH group showed stronger aversion than the THO group. Recently, we showed an enhanced aversion in penned dogs using levamisole plus an odor cue, increasing the strength and time to extinction in a taste‐potentiated odor aversion procedure. It has been suggested that the strong flavor of levamisole acted as a strong cue enhancing the aversion to the weaker cue, the vanilla odor .…”
Section: Discussioncontrasting
confidence: 99%
“…Recently, we showed an enhanced aversion in penned dogs using levamisole plus an odor cue, increasing the strength and time to extinction in a taste‐potentiated odor aversion procedure. It has been suggested that the strong flavor of levamisole acted as a strong cue enhancing the aversion to the weaker cue, the vanilla odor . Differences to the results of the present study could be explained because thiram was apparently not detected by dogs, acting both the food taste and odor as weak cues of the conditioning process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CFA can be induced deliberately by adding a chemical substance to the food or prey desired to be protected from predation in order to produce rejection by the predator (Gustavson et al ., 1974; Cowan et al ., 2000; O’Donnell, Webb & Shine, 2010). Recent studies carried out with captive dogs Canis familiaris and Iberian wolves Canis lupus signatus have shown the possibility of creating aversion by adding an artificial odor cue during conditioning (Tobajas et al ., 2019 a ; Tobajas et al ., unpublished data), thus, creating an enhanced aversion to that odor rather than to the food itself (Tobajas et al ., 2019 b ). This enables the predator to detect that a prey is noxious at a distance (Rusiniak et al ., 1979), and makes it possible to employ this disruptive effect caused by the odor aversion to stop predation during predatory behavior (Tobajas et al ., 2019 b ; Tobajas et al ., unpublished data).…”
Section: Introductionmentioning
confidence: 98%